(3GdYbO GdWgeGSjIs - (3MSjf Hf YHO GdUeO Hf eMeO GdLHYj (B((3HVe aaJM(B) (3GdYGedj GdMGQKj GdgeOGfqj,J (B984 (3g` s ((3eMeO Hf eMeO Ydi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CfRd ef GdSeGA eGA WghQkG hHYO ajbhd deG hQOJ EdG GdeSOOI GdeDjOI GdWgGQI s
(3BNQgG (B:s
(3Gdgee GdYGdjI Edi efGRd GdebQHjf hJQVi Efg LhGO cQje s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B15s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B240 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B17s
Keywords: (3GdeLGejYs